2020
DOI: 10.1097/qad.0000000000002470
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of scale-up to dolutegravir-based regimens in sub-Saharan Africa

Abstract: Objective: Evaluate the potential effectiveness of the implementation of dolutegravir (DTG)-based regimens in patients on failing current antiretroviral treatment (ART) given the high levels of nucleoside reverse transcriptase inhibitor (NRTI) resistance in Togo. Design: Patients on ART attending health facilities for routine follow-up visits and for whom HIV viral load test was performed were consecutively included. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…28,29 There has been concern that NRTI resistance associated with prior failing ART regimens may result in functional monotherapy with DTG in ART-experienced, virally unsuppressed individuals who switch to DTG and maintain the NRTI backbone of the failing regimen, potentially resulting in DTG failure and development of INSTI resistance. 30,31 However, meaningful differences in VLS between children who maintained or switched NRTI backbones at the time of the DTG switch were not observed in our study. This supports other evidence that found no difference among children virally unsuppressed before the single-drug switch to DTG when comparing small numbers on ABC, AZT or TDF-based backbones.…”
Section: Discussioncontrasting
confidence: 72%
“…28,29 There has been concern that NRTI resistance associated with prior failing ART regimens may result in functional monotherapy with DTG in ART-experienced, virally unsuppressed individuals who switch to DTG and maintain the NRTI backbone of the failing regimen, potentially resulting in DTG failure and development of INSTI resistance. 30,31 However, meaningful differences in VLS between children who maintained or switched NRTI backbones at the time of the DTG switch were not observed in our study. This supports other evidence that found no difference among children virally unsuppressed before the single-drug switch to DTG when comparing small numbers on ABC, AZT or TDF-based backbones.…”
Section: Discussioncontrasting
confidence: 72%
“…20 Similarly, up to 31% and 47.6% of patients after VL failure and ART switch to a DTG-based or blind switching without prior VL testing respectively were estimated to be on functional DTG monotherapy in a recent (2020) study carried out in Togo. 21 Although, we found high rate of VS on TLD, one of the limitations of our study is that the study follow-up period was short (median = 6.9 months). Therefore, the long-term effect of DTG-based regimens on viral suppression in this cohort is yet to be evaluated.…”
Section: Discussionmentioning
confidence: 65%
“…Suboptimal adherence to ART has long been identified as a major contributor to the development of drug resistance among people living with HIV [27,28]. Despite the higher genetic barrier in DTG, several studies have reported on the emergence of integrase inhibitor drug resistance and reduced efficacy in patients on DTG receiving functional monotherapy [29,30]. Viral failure in children and adolescents living with perinatally acquired HIV can be either the result of poor adherence, frequent in this population, or also often the consequence of pre-treatment drug resistance caused by suboptimal maternal ART regimens [31].…”
Section: Discussionmentioning
confidence: 99%